Sure! Let's solve the equation \( 5x + 8 + x = 32 \) step by step.
Step 1: Combine like terms on the left side. We have \( 5x \) and \( x \). We know that \( x \) is the same as \( 1x \), so we can write it as:
\[ 5x + 1x + 8 = 32 \]
Now, combine \( 5x \) and \( 1x \):
\[ 6x + 8 = 32 \]
Step 2: Subtract 8 from both sides. To isolate the \( 6x \), we need to get rid of the \( 8 \):
\[ 6x + 8 - 8 = 32 - 8 \]
This simplifies to:
\[ 6x = 24 \]
Step 3: Divide both sides by 6. We want to solve for \( x \), so we divide:
\[ \frac{6x}{6} = \frac{24}{6} \]
This gives us:
\[ x = 4 \]
So the solution is \( x = 4 \).
Step 4: Check your answer. Now let's check if \( x = 4 \) works in the original equation:
Substitute \( x \) back into the equation \( 5x + 8 + x = 32 \):
\[ 5(4) + 8 + 4 = 32 \]
Calculating this step by step:
- \( 5(4) = 20 \)
- Then add \( 8 \): \( 20 + 8 = 28 \)
- Finally add \( 4 \): \( 28 + 4 = 32 \)
Since both sides are equal, \( 32 = 32 \), our solution is correct!
So the final answer is:
\[ \boxed{4} \]